A revolução de 1930 em Itararé: o cinema documentário no ensino de história. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The present dissertation aims to analyze how the production of the documentary entitled “A Batalha Que o Rio Cavou” happened. The film addresses how the city of Itararé experienced the so-called Revolution of 1930, becoming known, therefore, as “the battle that did not take place”. The choices made in the production of the documentary are influenced by the social context in which this production is inserted, so it was first necessary to analyze the memories of the conflict in the city, especially through the memorialist productions and their cleavages with academic historiography. After analyzing the documentary, in its relations with the use of this genre of cinema in the teaching of History, a proposal is presented for a notebook of activities to be used by teachers for the teaching of history, whether local or the themes of the First Republic. in Brazil. Finally, we consider that both the film and the activity book allow another look at the 1930 Revolution in Itararé.
Keywords: Itararé; Historiografia; Memórias; Cinema; Documentário; Ensino de história; Itararé; Historiography; Memoirs; Movie Theater; Documentary; Teaching History; CNPQ::CIENCIAS HUMANAS::HISTORIA